2019
DOI: 10.17582/journal.aavs/2019/7.9.791.797
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Escherichia Coli in Pork Sold at Tamiang Layang Market, East Barito District

Abstract: provide a promising prospect for the people of East Barito. Unfortunately, many traditional markets in East Barito do not yet have special kiosks for the sale of pork. Currently, pork in East Barito sold on the roadside of the Tamiang Layang Market. The condition can cause the pork directly exposed to the sun, rain, dust, and other contaminants from the highway, which further may affect the pork quality. Food that sold openly on the roadside has a higher chance of being contaminated by coliform bacteria and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…[ 4 ] showed that antibiotics are mostly used in pig farms for medication (55.21%), disease prevention (42.71%), and enhanced production (2.08%). Antibiotics of tetracycline class (oxytetracycline and tetracycline) are frequently used in pig farms [ 4 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 ] showed that antibiotics are mostly used in pig farms for medication (55.21%), disease prevention (42.71%), and enhanced production (2.08%). Antibiotics of tetracycline class (oxytetracycline and tetracycline) are frequently used in pig farms [ 4 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of antibiotic-resistant E. coli in pigs might cause contamination of the pork [66], processed meat products [68], and pig slaughterhouse environment and its waste [38], in addition to having the potential to transmit to a wider area and ecosystem [57,58,69]. Marshall and Levy [70] and Sanders et al [11] showed that ARGs could be distributed to agricultural lands by direct and indirect contact through food, water, and animal feces.…”
Section: Distribution Of Tetracycline Resistance Genesmentioning
confidence: 99%
“…The occurrence of antibiotic-resistant E. coli in pigs poses a significant risk, as it can lead to the contamination of pork [ 66 ] and processed meat products [ 71 ], as well as aquatic [ 27 ] and terrestrial environments [ 72 ] through improper handling of waste generated. Based on the field survey, most pig farms in Banten province were close to community settlements, and the generated waste was not handled properly.…”
Section: Discussionmentioning
confidence: 99%
“…This high diversity indicated the spread of tet genes from pig farms to the environment due to the excessive and uncontrolled use of tetracycline antibiotics in farms. Tetracycline antibiotics such as oxytetracycline and tetracycline have been frequently used in Indonesian pig farms for both therapeutic and nontherapeutic purposes (prophylactic, metaphylactic) as well as for growth promotion [9,65,66]. According to Kallau et al [9], 55.21% of antibiotics in pig farms were used for treatment, whereas 42.71% and 2.08% were used for disease prevention and production enhancement, respectively.…”
Section: Detection Of Tetracycline Resistance Genesmentioning
confidence: 99%
“…Research conducted by Adzitey (2015) on contaminated beef in Ghana showed that E. coli isolates have resistance to vancomycin and erythromycin as well. Rizaldi et al (2019) found 17 samples of pork sold in the Tamiang Layang market were contaminated with E. coli and were resistant to erythromycin, streptomycin, penicillin G, chloramphenicol (100%), tetracycline (94.1%), ampicillin (76.5%), and acid nalidixate (23.5%). In addition, in an analysis of products sold at meat stalls in Tamaulipas, Mexico, Martınez-Vazquez et al (2018) reported that 73 E. coli strains obtained from beef samples and 85 E. coli strains obtained from pork samples were resistant to cephalothin, ampicillin, cefotaxime, nitrofurantoin, and tetracycline antibiotics.…”
Section: Antibiotic Resistance In Escherichia Colimentioning
confidence: 99%